Influence of workload and recovery on injuries in elite male volleyball players - Timoteo, T. F.; Debien, P. B.; Miloski, B.; Werneck, F. Z.; Gabbett, T.; Bara Filho, M. G. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to investigate the influence of workload and recovery on injury rates in elite male volleyball players. Data were collected from 14 male professional volleyball players over a 27-week season. Workloads were monitored daily using the session rating of perceived exertion, and recovery status was appraised using the Total Quality Recovery (TQR) scale. The players were exposed to 4,573.31 hours (h) of training and games with an overall injury incidence of 13.99 per 1,000 hours. Overuse accounted for 83% (11.58 injuries/1,000 hours) and trauma accounted for 17% (2.40 injuries per 1,000 hours) of all injuries. There was a higher incidence of injuries (p = 0.003), higher weekly workload (p = 0.008), and acute:chronic workload ratio (ACWR) (p < 0.001) in the pre-season compared with the competitive period. Healthy players had lower ACWR (p = 0.002) compared with the injured players. The TQR was higher for the healthy group compared with the injured group (p < 0.001). The greater odds of injury was related to higher ACWR (risk factor) (p = 0.014) and lower TQR values (p = 0.004) (protection factor). Athlete's workloads and the state of recovery may be related to injuries in volleyball. The results presented in this study emphasize the importance of controlling these variables in professional volleyball teams to prevent injuries.